Team:Groningen/Modelling/Arsenic

From 2009.igem.org

(Difference between revisions)
(Equilibrium: Equilibrium computations (without overexpression).)
(Introduced difference between natural operators and operators added by us (Groningen).)
Line 18: Line 18:
* Intracellular:
* Intracellular:
** As(III)
** As(III)
-
** Operator (concentration of unbound operators)
+
** OpN (concentration of unbound operators)
 +
** OpG (concentration of unbound operators that we introduce)
** <del>As(V)</del>
** <del>As(V)</del>
** <del>ArsC</del>
** <del>ArsC</del>
Line 26: Line 27:
*** At equilibrium: ArsR As(III) = (k1<sub>off</sub>/k1<sub>on</sub>) ArsR<sub>As</sub>
*** At equilibrium: ArsR As(III) = (k1<sub>off</sub>/k1<sub>on</sub>) ArsR<sub>As</sub>
** ArsD<sub>As</sub> (bound to As(III))
** ArsD<sub>As</sub> (bound to As(III))
-
** ArsR<sub>op</sub> (bound to operator)
+
** ArsR<sub>opn</sub> (bound to operator)
-
** ArsD<sub>op</sub> (bound to operator)
+
** ArsD<sub>opn</sub> (bound to operator)
 +
** ArsR<sub>opg</sub> (bound to opg)
 +
** ArsD<sub>opg</sub> (bound to opg)
The variables above can be related to each other through the following "reactions" and/or equations:
The variables above can be related to each other through the following "reactions" and/or equations:
Line 36: Line 39:
* As(III)<sub>in</sub> + ArsR &harr; ArsR<sub>As</sub>
* As(III)<sub>in</sub> + ArsR &harr; ArsR<sub>As</sub>
* As(III)<sub>in</sub> + ArsD &harr; ArsD<sub>As</sub>
* As(III)<sub>in</sub> + ArsD &harr; ArsD<sub>As</sub>
-
* Operator + ArsR &harr; ArsR<sub>op</sub>
+
* OpN + ArsR &harr; ArsR<sub>opn</sub>
-
* Operator + ArsD &harr; ArsD<sub>op</sub>
+
* OpN + ArsD &harr; ArsD<sub>opn</sub>
-
* Operator &rarr; Operator + ArsR + ArsD (transcription + translation)
+
* OpG + ArsR &harr; ArsR<sub>opg</sub>
 +
* OpG + ArsD &harr; ArsD<sub>opg</sub>
 +
* OpN &rarr; OpN + ArsR + ArsD (transcription + translation)
 +
* OpG &rarr; OpG + ArsR (transcription + translation)
* ArsR &rarr; null (degradation)
* ArsR &rarr; null (degradation)
* ArsD &rarr; null (degradation)
* ArsD &rarr; null (degradation)
Line 45: Line 51:
* (d/dt) As(III) = - (k1<sub>on</sub> ArsR+k2<sub>on</sub> ArsD) As(III) + k1<sub>off</sub> ArsR<sub>As</sub> + k2<sub>off</sub> ArsD<sub>As</sub>
* (d/dt) As(III) = - (k1<sub>on</sub> ArsR+k2<sub>on</sub> ArsD) As(III) + k1<sub>off</sub> ArsR<sub>As</sub> + k2<sub>off</sub> ArsD<sub>As</sub>
-
* (d/dt) Operator = - (k3<sub>on</sub> ArsR+k4<sub>on</sub> ArsD) Operator + k3<sub>off</sub> ArsR<sub>op</sub> + k3<sub>off</sub> ArsD<sub>op</sub>
+
* (d/dt) OpN = - (k3<sub>on</sub> ArsR+k4<sub>on</sub> ArsD) OpN + k3<sub>off</sub> ArsR<sub>opn</sub> + k3<sub>off</sub> ArsD<sub>opn</sub>
-
* (d/dt) ArsR = &beta;1 Operator - (ln(2)/&tau;1+k1<sub>on</sub> As(III)+k3<sub>on</sub> Operator) ArsR + k1<sub>off</sub> ArsR<sub>As</sub> + k3<sub>off</sub> ArsR<sub>op</sub>
+
* (d/dt) OpG = - (k3<sub>on</sub> ArsR+k4<sub>on</sub> ArsD) OpG + k3<sub>off</sub> ArsR<sub>opg</sub> + k3<sub>off</sub> ArsD<sub>opg</sub>
-
* (d/dt) ArsD = &beta;2 Operator - (ln(2)/&tau;2+k2<sub>on</sub> As(III)+k4<sub>on</sub> Operator) ArsD + k2<sub>off</sub> ArsD<sub>As</sub> + k4<sub>off</sub> ArsD<sub>op</sub>
+
* (d/dt) ArsR = &beta;1 (OpN+OpG) - (ln(2)/&tau;1+k1<sub>on</sub> As(III)+k3<sub>on</sub> (OpN+OpG)) ArsR + k1<sub>off</sub> ArsR<sub>As</sub> + k3<sub>off</sub> (ArsR<sub>opn</sub>+ArsR<sub>opg</sub>)
 +
* (d/dt) ArsD = &beta;2 OpN - (ln(2)/&tau;2+k2<sub>on</sub> As(III)+k4<sub>on</sub> (OpN+OpG)) ArsD + k2<sub>off</sub> ArsD<sub>As</sub> + k4<sub>off</sub> (ArsD<sub>opn</sub>+ArsD<sub>opg</sub>)
* (d/dt) ArsR<sub>As</sub> = k1<sub>on</sub> ArsR As(III) - k1<sub>off</sub> ArsR<sub>As</sub>
* (d/dt) ArsR<sub>As</sub> = k1<sub>on</sub> ArsR As(III) - k1<sub>off</sub> ArsR<sub>As</sub>
* (d/dt) ArsD<sub>As</sub> = k2<sub>on</sub> ArsD As(III) - k2<sub>off</sub> ArsD<sub>As</sub>
* (d/dt) ArsD<sub>As</sub> = k2<sub>on</sub> ArsD As(III) - k2<sub>off</sub> ArsD<sub>As</sub>
-
* (d/dt) ArsR<sub>op</sub> = k3<sub>on</sub> ArsR Operator - k3<sub>off</sub> ArsR<sub>op</sub>
+
* (d/dt) ArsR<sub>opn</sub> = k3<sub>on</sub> ArsR OpN - k3<sub>off</sub> ArsR<sub>opn</sub>
-
* (d/dt) ArsD<sub>op</sub> = k4<sub>on</sub> ArsD Operator - k4<sub>off</sub> ArsD<sub>op</sub>
+
* (d/dt) ArsD<sub>opn</sub> = k4<sub>on</sub> ArsD OpN - k4<sub>off</sub> ArsD<sub>opn</sub>
 +
* (d/dt) ArsR<sub>opg</sub> = k3<sub>on</sub> ArsR OpG - k3<sub>off</sub> ArsR<sub>opg</sub>
 +
* (d/dt) ArsD<sub>opg</sub> = k4<sub>on</sub> ArsD OpG - k4<sub>off</sub> ArsD<sub>opg</sub>
Using the following constants/definitions:
Using the following constants/definitions:
Line 76: Line 85:
<pre>
<pre>
0 = - (k1on ArsR+k2on ArsD) As(III) + k1off ArsRAs + k2off ArsDAs
0 = - (k1on ArsR+k2on ArsD) As(III) + k1off ArsRAs + k2off ArsDAs
-
0 = - (k3on ArsR+k4on ArsD) Operator + k3off ArsRop + k3off ArsDop
+
0 = - (k3on ArsR+k4on ArsD) OpN + k3off ArsRopn + k3off ArsDopn
-
0 = β1 Operator - (ln(2)/τ1+k1on As(III)+k3on Operator) ArsR + k1off ArsRAs + k3off ArsRop
+
0 = - (k3on ArsR+k4on ArsD) OpG + k3off ArsRopg + k3off ArsDopg
-
0 = β2 Operator - (ln(2)/τ2+k2on As(III)+k4on Operator) ArsD + k2off ArsDAs + k4off ArsDop
+
0 = β1 (OpN+OpG) - (ln(2)/τ1+k1on As(III)+k3on (OpN+OpG)) ArsR + k1off ArsRAs + k3off (ArsRopn+ArsRopg)
 +
0 = β2 OpN - (ln(2)/τ2+k2on As(III)+k4on (OpN+OpG)) ArsD + k2off ArsDAs + k4off (ArsDopn+ArsDopg)
0 = k1on ArsR As(III) - k1off ArsRAs
0 = k1on ArsR As(III) - k1off ArsRAs
0 = k2on ArsD As(III) - k2off ArsDAs
0 = k2on ArsD As(III) - k2off ArsDAs
-
0 = k3on ArsR Operator - k3off ArsRop
+
0 = k3on ArsR OpN - k3off ArsRopn
-
0 = k4on ArsD Operator - k4off ArsDop
+
0 = k4on ArsD OpN - k4off ArsDopn
 +
0 = k3on ArsR OpG - k3off ArsRopg
 +
0 = k4on ArsD OpG - k4off ArsDopg
</pre>
</pre>
-
By eliminating the last four equations from the rest and dividing the last four by kNon we are left with:
+
From the last four equations it can be seen that the ratio between OpN and ArsR<sub>opn</sub> should be equal to the ratio between OpG and ArsR<sub>opg</sub>, and similarly for ArsD<sub>op?</sub>. This leads to:
<pre>
<pre>
-
0 = β1 Operator - (ln(2)/τ1) ArsR
+
    Op = OpN + OpG
-
0 = β2 Operator - (ln(2)/τ2) ArsD
+
OpN/OpG = OpNT/OpGT
 +
OpN/Op = OpNT/OpT
 +
ArsRop = ArsRopn + ArsRopg
 +
ArsDop = ArsDopn + ArsDopg
 +
 
 +
0 = - (k1on ArsR+k2on ArsD) As(III) + k1off ArsRAs + k2off ArsDAs
 +
0 = - (k3on ArsR+k4on ArsD) Op + k3off ArsRop + k3off ArsDop
 +
0 = β1 Op - (ln(2)/τ1+k1on As(III)+k3on Op) ArsR + k1off ArsRAs + k3off ArsRop
 +
0 = β2 OpN - (ln(2)/τ2+k2on As(III)+k4on Op) ArsD + k2off ArsDAs + k4off ArsDop
 +
0 = k1on ArsR As(III) - k1off ArsRAs
 +
0 = k2on ArsD As(III) - k2off ArsDAs
 +
0 = k3on ArsR Op - k3off ArsRop
 +
0 = k4on ArsD Op - k4off ArsDop
 +
</pre>
 +
 
 +
By eliminating the last four equations from the rest and dividing the last four by k?on we are left with:
 +
 
 +
<pre>
 +
0 = β1 Op - (ln(2)/τ1) ArsR
 +
0 = β2 OpN - (ln(2)/τ2) ArsD
0 = ArsR As(III) - K1d ArsRAs
0 = ArsR As(III) - K1d ArsRAs
0 = ArsD As(III) - K2d ArsDAs
0 = ArsD As(III) - K2d ArsDAs
-
0 = ArsR Operator - K3d ArsRop
+
0 = ArsR Op - K3d ArsRop
-
0 = ArsD Operator - K4d ArsDop
+
0 = ArsD Op - K4d ArsDop
</pre>
</pre>
-
Using the fact that the total amount of operators remains constant the last two equations can be used to derive an equation for Operator:
+
Using the fact that the total amount of operators remains constant the last two equations can be used to derive an equation for Op:
<pre>
<pre>
-
     0 = ArsR Operator - K3d ArsRop
+
     0 = ArsR Op - K3d ArsRop
-
     0 = ArsR Operator - K3d (OperatorT - Operator - ArsDop)
+
     0 = ArsR Op - K3d (OpT - Op - ArsDop)
-
     0 = (ArsR + K3d) Operator - K3d OperatorT + K3d ArsDop
+
     0 = (ArsR + K3d) Op - K3d OpT + K3d ArsDop
-
     0 = (ArsR/K3d + 1) Operator - OperatorT + ArsDop
+
     0 = (ArsR/K3d + 1) Op - OpT + ArsDop
-
ArsDop = OperatorT - (ArsR/K3d + 1) Operator
+
ArsDop = OpT - (ArsR/K3d + 1) Op
-
      0 = ArsD Operator - K4d ArsDop
+
0 = ArsD Op - K4d ArsDop
-
      0 = ArsD Operator - K4d (OperatorT - (ArsR/K3d + 1) Operator)
+
0 = ArsD Op - K4d (OpT - (ArsR/K3d + 1) Op)
-
      0 = (ArsD/K4d) Operator - OperatorT + (ArsR/K3d + 1) Operator
+
0 = (ArsD/K4d) Op - OpT + (ArsR/K3d + 1) Op
-
      0 = (ArsR/K3d + ArsD/K4d + 1) Operator - OperatorT
+
0 = (ArsR/K3d + ArsD/K4d + 1) Op - OpT
-
Operator = OperatorT/(ArsR/K3d + ArsD/K4d + 1)
+
Op = OpT/(ArsR/K3d + ArsD/K4d + 1)
</pre>
</pre>
Line 115: Line 146:
<pre>
<pre>
-
   0 = β1 Operator - (ln(2)/τ1) ArsR
+
   0 = β1 Op - (ln(2)/τ1) ArsR
-
   0 = β1 OperatorT - (ln(2)/τ1) ArsR (ArsR/K3d + ArsD/K4d + 1)
+
   0 = β1 OpT - (ln(2)/τ1) ArsR (ArsR/K3d + ArsD/K4d + 1)
-
   0 = β1 OperatorT - (ln(2)/τ1) ArsR&sup2;/K3d - (ln(2)/τ1) ArsR ArsD/K4d - (ln(2)/τ1) ArsR
+
   0 = β1 OpT - (ln(2)/τ1) ArsR&sup2;/K3d - (ln(2)/τ1) ArsR ArsD/K4d - (ln(2)/τ1) ArsR
-
   0 = K3d (τ1/ln(2)) β1 OperatorT - ArsR&sup2; - (K3d/K4d) ArsD ArsR - K3d ArsR
+
   0 = K3d (τ1/ln(2)) β1 OpT - ArsR&sup2; - (K3d/K4d) ArsD ArsR - K3d ArsR
-
   0 = &frac12; ArsR&sup2; + &frac12; K3d (ArsD/K4d + 1) ArsR - &frac12; K3d (τ1/ln(2)) β1 OperatorT
+
   0 = &frac12; ArsR&sup2; + &frac12; K3d (ArsD/K4d + 1) ArsR - &frac12; K3d (τ1/ln(2)) β1 OpT
ArsR = -b1 &plusmn; &radic;(b1&sup2; + c1)
ArsR = -b1 &plusmn; &radic;(b1&sup2; + c1)
   b1 = &frac12; K3d (ArsD/K4d + 1)
   b1 = &frac12; K3d (ArsD/K4d + 1)
-
   c1 =  K3d (τ1/ln(2)) β1 OperatorT
+
   c1 =  K3d (τ1/ln(2)) β1 OpT
-
   0 = β2 OperatorT - (ln(2)/τ2) ArsD (ArsR/K3d + ArsD/K4d + 1)
+
   0 = β2 OpN - (ln(2)/τ2) ArsD
 +
  0 = β2 OpNT - (ln(2)/τ2) ArsD (ArsR/K3d + ArsD/K4d + 1)
ArsD = -b2 &plusmn; &radic;(b2&sup2; + c2)
ArsD = -b2 &plusmn; &radic;(b2&sup2; + c2)
   b2 = &frac12; K4d (ArsR/K3d + 1)
   b2 = &frac12; K4d (ArsR/K3d + 1)
-
   c2 =  K4d (τ2/ln(2)) β2 OperatorT
+
   c2 =  K4d (τ2/ln(2)) β2 OpNT
</pre>
</pre>

Revision as of 13:06, 14 July 2009

Bold text

Igemhomelogo.png

Our initial ideas on how and what to model can be found at Brainstorm/Modelling.

Usage of graphs in wiki: Graphs

The raw model

Note: Math support is currently not enabled on this Wiki... (I've asked hq if they can enable it.)

The following variables play an important role in our system (these can be concentrations of substances, the density of the cell, etc.):

  • Extracellular:
    • As(III)
    • As(V)
  • Intracellular:
    • As(III)
    • OpN (concentration of unbound operators)
    • OpG (concentration of unbound operators that we introduce)
    • As(V)
    • ArsC
    • ArsR
    • ArsD
    • ArsRAs (bound to As(III))
      • At equilibrium: ArsR As(III) = (k1off/k1on) ArsRAs
    • ArsDAs (bound to As(III))
    • ArsRopn (bound to operator)
    • ArsDopn (bound to operator)
    • ArsRopg (bound to opg)
    • ArsDopg (bound to opg)

The variables above can be related to each other through the following "reactions" and/or equations:

  • As(V)ex → As(V), using phosphate transporters? (Summers2009)
  • As(V)ex → As(III), using ArsC (Summers2009)
  • As(III) → As(III)ex, using ArsAB (helped by ArsD) (Summers2009)
  • As(III)in + ArsR ↔ ArsRAs
  • As(III)in + ArsD ↔ ArsDAs
  • OpN + ArsR ↔ ArsRopn
  • OpN + ArsD ↔ ArsDopn
  • OpG + ArsR ↔ ArsRopg
  • OpG + ArsD ↔ ArsDopg
  • OpN → OpN + ArsR + ArsD (transcription + translation)
  • OpG → OpG + ArsR (transcription + translation)
  • ArsR → null (degradation)
  • ArsD → null (degradation)

Resulting in the following differential equations (please note that the first two can be formed by linear combinations of the other six):

  • (d/dt) As(III) = - (k1on ArsR+k2on ArsD) As(III) + k1off ArsRAs + k2off ArsDAs
  • (d/dt) OpN = - (k3on ArsR+k4on ArsD) OpN + k3off ArsRopn + k3off ArsDopn
  • (d/dt) OpG = - (k3on ArsR+k4on ArsD) OpG + k3off ArsRopg + k3off ArsDopg
  • (d/dt) ArsR = β1 (OpN+OpG) - (ln(2)/τ1+k1on As(III)+k3on (OpN+OpG)) ArsR + k1off ArsRAs + k3off (ArsRopn+ArsRopg)
  • (d/dt) ArsD = β2 OpN - (ln(2)/τ2+k2on As(III)+k4on (OpN+OpG)) ArsD + k2off ArsDAs + k4off (ArsDopn+ArsDopg)
  • (d/dt) ArsRAs = k1on ArsR As(III) - k1off ArsRAs
  • (d/dt) ArsDAs = k2on ArsD As(III) - k2off ArsDAs
  • (d/dt) ArsRopn = k3on ArsR OpN - k3off ArsRopn
  • (d/dt) ArsDopn = k4on ArsD OpN - k4off ArsDopn
  • (d/dt) ArsRopg = k3on ArsR OpG - k3off ArsRopg
  • (d/dt) ArsDopg = k4on ArsD OpG - k4off ArsDopg

Using the following constants/definitions:

  • K1d = k1off/k1on
  • K2d = k2off/k2on = 60µM (Chen1997)
  • K3d = k3off/k3on = 0.33µM (Chen1997, suspect as the relevant reference doesn't actually seem to give any value for this)
  • K4d = k4off/k4on = 65µM (Chen1997)
  • degradation rate = ln(2)/τ
  • ArsR half-life time = τ1
  • ArsD half-life time = τ2
  • β1 = β2 ??? (and either value is unknown)

See Chen1997 for the interplay between ArsR and ArsD.

TODO Figure out relevant equations for metallochaperone function of ArsD?

TODO Make sure all the multiplicities are correct (and/or taken care of in constants). E.g. does 1 mol ArsR (if it is bound) bind 1 mol As(III)?

Equilibrium

For many purposes, like determining the total amount of accumulated arsenic, it can be quite useful to consider the system at equilibrium. That is, when the derivatives of all variables to time are zero:

0 = - (k1on ArsR+k2on ArsD) As(III) + k1off ArsRAs + k2off ArsDAs
0 = - (k3on ArsR+k4on ArsD) OpN + k3off ArsRopn + k3off ArsDopn
0 = - (k3on ArsR+k4on ArsD) OpG + k3off ArsRopg + k3off ArsDopg
0 = β1 (OpN+OpG) - (ln(2)/τ1+k1on As(III)+k3on (OpN+OpG)) ArsR + k1off ArsRAs + k3off (ArsRopn+ArsRopg)
0 = β2 OpN - (ln(2)/τ2+k2on As(III)+k4on (OpN+OpG)) ArsD + k2off ArsDAs + k4off (ArsDopn+ArsDopg)
0 = k1on ArsR As(III) - k1off ArsRAs
0 = k2on ArsD As(III) - k2off ArsDAs
0 = k3on ArsR OpN - k3off ArsRopn
0 = k4on ArsD OpN - k4off ArsDopn
0 = k3on ArsR OpG - k3off ArsRopg
0 = k4on ArsD OpG - k4off ArsDopg

From the last four equations it can be seen that the ratio between OpN and ArsRopn should be equal to the ratio between OpG and ArsRopg, and similarly for ArsDop?. This leads to:

     Op = OpN + OpG
OpN/OpG = OpNT/OpGT
 OpN/Op = OpNT/OpT
 ArsRop = ArsRopn + ArsRopg
 ArsDop = ArsDopn + ArsDopg

0 = - (k1on ArsR+k2on ArsD) As(III) + k1off ArsRAs + k2off ArsDAs
0 = - (k3on ArsR+k4on ArsD) Op + k3off ArsRop + k3off ArsDop
0 = β1 Op - (ln(2)/τ1+k1on As(III)+k3on Op) ArsR + k1off ArsRAs + k3off ArsRop
0 = β2 OpN - (ln(2)/τ2+k2on As(III)+k4on Op) ArsD + k2off ArsDAs + k4off ArsDop
0 = k1on ArsR As(III) - k1off ArsRAs
0 = k2on ArsD As(III) - k2off ArsDAs
0 = k3on ArsR Op - k3off ArsRop
0 = k4on ArsD Op - k4off ArsDop

By eliminating the last four equations from the rest and dividing the last four by k?on we are left with:

0 = β1 Op - (ln(2)/τ1) ArsR
0 = β2 OpN - (ln(2)/τ2) ArsD
0 = ArsR As(III) - K1d ArsRAs
0 = ArsD As(III) - K2d ArsDAs
0 = ArsR Op - K3d ArsRop
0 = ArsD Op - K4d ArsDop

Using the fact that the total amount of operators remains constant the last two equations can be used to derive an equation for Op:

     0 = ArsR Op - K3d ArsRop
     0 = ArsR Op - K3d (OpT - Op - ArsDop)
     0 = (ArsR + K3d) Op - K3d OpT + K3d ArsDop
     0 = (ArsR/K3d + 1) Op - OpT + ArsDop
ArsDop = OpT - (ArsR/K3d + 1) Op

 0 = ArsD Op - K4d ArsDop
 0 = ArsD Op - K4d (OpT - (ArsR/K3d + 1) Op)
 0 = (ArsD/K4d) Op - OpT + (ArsR/K3d + 1) Op
 0 = (ArsR/K3d + ArsD/K4d + 1) Op - OpT
Op = OpT/(ArsR/K3d + ArsD/K4d + 1)

This leads to the following:

   0 = β1 Op - (ln(2)/τ1) ArsR
   0 = β1 OpT - (ln(2)/τ1) ArsR (ArsR/K3d + ArsD/K4d + 1)
   0 = β1 OpT - (ln(2)/τ1) ArsR²/K3d - (ln(2)/τ1) ArsR ArsD/K4d - (ln(2)/τ1) ArsR
   0 = K3d (τ1/ln(2)) β1 OpT - ArsR² - (K3d/K4d) ArsD ArsR - K3d ArsR
   0 = ½ ArsR² + ½ K3d (ArsD/K4d + 1) ArsR - ½ K3d (τ1/ln(2)) β1 OpT
ArsR = -b1 ± √(b1² + c1)
  b1 = ½ K3d (ArsD/K4d + 1)
  c1 =   K3d (τ1/ln(2)) β1 OpT

   0 = β2 OpN - (ln(2)/τ2) ArsD
   0 = β2 OpNT - (ln(2)/τ2) ArsD (ArsR/K3d + ArsD/K4d + 1)
ArsD = -b2 ± √(b2² + c2)
  b2 = ½ K4d (ArsR/K3d + 1)
  c2 =   K4d (τ2/ln(2)) β2 OpNT

As b1 and b2 are positive (concentrations are always non-negative) only the plus signs in the two plus-minuses above are valid choices. In addition, since c1 and c2 are non-negative the square roots are always larger than or equal to b1/b2, leading to non-negative values for ArsR/ArsD. The equations for ArsR and ArsD derived above can be used in a fixed point iteration as follows:

f(ArsR) = -b1 + √(b1² + c1)
  with ArsD = -b2 + √(b2² + c2)

   f' = -b1' + (2 b1 b1')/√(b1² + c1)
  b1' = ½ (K3d/K4d) ArsD'
ArsD' = -b2' + (2 b2 b2')/√(b2² + c2)
  b2' = ½ (K4d/K3d)

Assuming that the total amount of arsenic in the cell is also constant the following equation can be derived for arsenic, analogous to the derivation of the equation for Operator:

ArsR As(III) = K1d ArsRAs
ArsD As(III) = K2d ArsDAs
As(III)T = As(III) + ArsRAs + ArsDAs

As(III)/As(III)T = 1/(ArsR/K1d + ArsD/K2d + 1)

Kinetic Laws

TODO Add references.

TODO Find out how to determine experimentally which is applicable (and if you know, what the parameters are).

Mass Action
Molecules randomly interact, the reaction rate is simply the product of the concentrations of the reactants (multiplied by a constant).
Michaelis-Menten
Applicable to situations where there is a maximum reaction rate (due to needing a catalyst/transporter/binding site of which there is only a limited amount for example) under the assumption that there is much more of the "main" reactant than of the catalyst/transporter. Has two constants, the maximum reaction rate and the concentration at which the reaction rate is half the maximum reaction rate.
Michaelis-Menten reversible
TODO
Hill
Generalization of Michaelis-Menten. More detail.